Watershed hydrology, management and modeling - Yousuf, Abrar, 1989-; Singh, Manmohanjit, 1971- (Boca Raton : CRC Press, 2019)
The book provides a comprehensive insight into watersheds and modeling of the hydrological processes in the watersheds. It covers the concepts of watershed hydrology and watershed management in depth. The basic types, of soil erosion and its measurement and estimation of runoff and soil loss from the small and large watersheds are discussed. Recent advances in the watershed management like the application of remote sensing and GIS and hydrological models are a part of the book. The book serve as a guide for professional and competitive examinations for undergraduate students of Agriculture and Agricultural Engineering and graduate students of Soil Science, Soil and Water Engineering, Agricultural Physics, Hydrology and Watershed Management.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Environmental Science; SCIENCE / Life Sciences / General; TECHNOLOGY / Environmental Engineering & Technology; Watershed hydrology; Watershed management; Soil erosion